KONSEP PENDIDIKAN AKHLAK PERSPEKTIF SYAIKH MUHAMMAD SYAKIR & UMAR BIN ACHMAD BARADJA: The Concept Of Moral Education From The Perspective Of Shaykh Muhammad Syakir & Umar Bin Achmad Baradja - Agam Gunawan; Asep Muhyidin (STAI Ma'had Aly Al-Hikam Malang, 2025)
The aim of this study is to analyze the concept of moral education according to Shaykh Muhammad Syakir compared with the concept of moral education according to Shaykh Umar Bin Achmad Baradja in the book Waşāyā Al-Ābā’ Lil Abnā’ and books Al-Akhlaq Lil Banin’ The following are the differences and similarities. This research method uses a qualitative approach with a character study method. The data sources in this study are primary and secondary data. This study found that the concept of moral education of Syaikh Muhammad Syakir in the book Waşāyā Al-Ābā’ Lil Abnā’ includes several concepts, namely the concept of morality towards Allah and His Messenger, morality towards oneself, morality towards parents, teachers, and friends, and the concept of morality towards other people and society. Meanwhile, the concept of moral education of Sheikh Umar Bin Achmad Baradja in the book Al-Akhlaq Lil Banin’ includes several concepts, namely the concept of loved students, student morals before going to school, student morals on the way, student morals in school, student morals in maintaining school equipment, student morals towards teachers, and student morals towards friends. The differences lie in the discussion, student situations, nuances of thought, student morals in preparation before learning, student morals when dealing with teachers, and student morals when dealing with friends. The similarities lie in important points, namely regarding the purpose of seeking knowledge, morals towards teachers which include morals of respecting teachers, morals when studying and morals of being patient with the harsh behavior of teachers, and morals towards friends.